Fibroblast mitogenic activity of lung lavage fluid from infants with chronic lung disease of prematurity. Issue 3 (1st May 2002) - Currie, A E; Kelly, M; Vyas, J R; Pandya, H; Field, D; Kotecha, S
Abstract : Background: Lung fibrosis is thought to be important in chronic lung disease of prematurity (CLD). Methods: Fibroblast proliferative activity was assessed in 207 bronchoalveolar lavage fluid (BALF) samples from 43 infants. Sixteen developed CLD (birth weight 765 g (630–1230), gestation 26.5 weeks (23–29)), 18 developed respiratory distress syndrome (RDS) (birth weight 1415 g (430–4160), gestation 31 weeks (23–39)), and nine control infants (birth weight 2110 g (900–3720), gestation 32 weeks (26–41)) received mechanical ventilation for non-pulmonary reasons. Results: The fibroblast proliferative activity relative to 10% fetal calf serum was 64–75% in infants with CLD, 55–86% in the RDS group, and 42–68% in control infants during the first 5 weeks of life. Only at day 3 was there a difference between the groups (CLD 72% v control 42%, p < 0.01; RDS 63% v control 42%, p < 0.05). With the use of neutralising antibodies, platelet derived growth factor BB (PDGF-BB) and epidermal growth factor were undetectable, and insulin-like growth factor I (IGF-I) accounted for 14% (p < 0.05) and 11% (p < 0.005) of BALF mitogenic activity from the RDS and CLD groups respectively. Conclusions: The mitogenic activity of BALF was similar in the three groups studied and was only partially accounted for by IGF-I. Growth factors other than PDGF-BB and IGF-I contribute significantly to this process.